Tolerant to humans? Assessment of alert and flight initiation distances of two bird species in relation to sex, flock size, and environmental characteristics. Issue 5 (2nd September 2020) - García-Arroyo, Michelle; MacGregor-Fors, Ian
Abstract : Birds invest time and resources in escape behaviors, thus changing their foraging strategies, habitat selection, and even reproduction. Flight initiation distance (FID) and the distance at which birds detect a threat, alert distance (AD), have been used as indicators of the ability of birds to detect potential predators. In this study we compared the two aforementioned measures of risk reaction for the House sparrow and the Orange-breasted bunting, two bird species inhabiting the same urban areas, and assessed if they were related with sex, flock size, and environmental factors. We performed generalized linear mixed models (GLMM) to explore the relationships between environmental factors and ADs and FIDs. Both behavioral responses were significantly lower for House sparrows. Although we did not find significant relationships between the assessed variables (sex, flock size, environmental factors) and bunting ADs and FIDs, we did find House sparrow males to be bolder (showing shorter ADs and FIDs), as well as larger ADs and FIDs for sparrows with increasing flock size. House sparrow ADs and FIDs were positively related with herbaceous plant cover and negatively related with minimum building height. In general, House sparrows showed to be bolder than Orange-breasted buntings, with differential responses of the sparrow related with sex, flock size, and different environmental factors. Having recorded bolder House sparrow males could be due to increases in aggressiveness related to the breeding season. Our results add to the lacking behavioral information available for the endemic Orange-breasted bunting and provide insights on the variation of the behavior of House sparrows in small urban areas.